Mindfulness-Based Stress Reduction (MBSR) as a Standalone Intervention for Posttraumatic Stress Disorder after Mixed Traumatic Events: A Mixed-Methods Feasibility Study - Müller-Engelmann, Meike; Wünsch, Susanne; Volk, Marina; Steil, Regina (Frontiers in Psychology, 2017)
Objectives: There is promising evidence that mindfulness-based interventions are effective in reducing symptoms of posttraumatic stress disorder (PTSD). However, until now, studies often lack a full clinical PTSD assessment and interventions are often administered in addition to other interventions. This study examined the feasibility of mindfulness-based stress reduction (MBSR) in patients with PTSD after experiencing mixed traumatic events as a standalone intervention. Method: 14 patients participated in 8 weeks of MBSR. The effects of the intervention were assessed prior to treatment, post-treatment and at one-month follow-up through self-ratings (e.g. the Davidson Trauma Scale) and the Clinician-Administered PTSD Scale. Furthermore, after the intervention, patients participated in qualitative interviews regarding their experiences with MBSR and their ideas for future improvements. Results: Nine patients finished the program, and these patients considered the exercises to be applicable and helpful. In the Clinician-Administered PTSD Scale, we found large effects regarding the reduction in PTSD symptoms among completers (Cohen’s d =1.2). In the Davidson Trauma Scale, the effect sizes were somewhat lower (Cohen’s d =0.6) but nevertheless confirmed the efficacy of MBSR in reducing PTSD symptoms. In the qualitative interviews, patients reported an augmentation of wellbeing and improvement regarding the handling of difficult situations as well as more distance from the traumatic event. Conclusion: Despite the large effects, the high dropout rates and the results of the post interviews suggest that the intervention should be better adapted to the needs of PTSD patients, e.g. by giving more information regarding the exercises and by including shorter exercises to manage acute distress.